Antioxidant properties and phenolic profile of the most widely appreciated cultivated mushrooms: a comparative study between in vivo and in vitro samples. - Reis, Filipa S. (2012)
The present study reports a comparison of the antioxidant properties and phenolic profile of the most consumed species as fresh cultivated mushrooms and their mycelia produced in vitro: Agaricus bisporus (white and brown), Pleurotus ostreatus (oyster), Pleurotus eryngii (king oyster) and Lentinula edodes (shiitake). The antioxidant activity was evaluated through reducing power (Folin-Ciocalteu and Ferricyanide/Prussian blue assays), free radical scavenging activity (DPPH assay) and lipid peroxidation inhibition (β-carotene/linoleate and TBARS assays). The analysis of phenolic compounds was performed by HPLC/PAD. The mushroom species with the highest antioxidant potential was Agaricus bispous (brown). However, concerning to the species obtained in vitro, it was Lentinula edodes that demonstrate the highest reducing power. Generally, in vivo samples revealed higher antioxidant properties than their mycelia obtained by in vitro techniques. About the phenolic compounds researched, they were detected both in mushrooms and mycelia without any particular abundance. Results showed that there is no correlation between the studied commercial mushrooms and the corresponding mycelia obtained in vitro. Nevertheless, this study contributes to the rise of data relatively to the species consumed as fresh mushrooms and the possibility of their in vitro production as a source of bioactive compounds.